Needs Analysis of English for Aeronautical Engineering Purposes at STT Adisutjipto Yogyakarta - Pertiwi, Dewanti Ratna (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2016)
In the context of ESP, needs analysis is the first step to develop a program. Needs analysis is conducted to investigate the present students mastery and the need of the future work field. This study aims to investigate the needs analysis of English for aeronautical engineering. The study employed a survey technique in the form of distributing questionnaires and interview for the lecturers, and centre of quality insurance. Indonesian qualification framework to standardize the graduate of aeronautical engineering with the national criteria is used as the source of developing the research instruments. The result of the study is expected to be able to build the foundation of developing better English course for aeronautical engineering students.